A Case of Vitiligo Combined with Systemic Lupus Erythematosus Treated with Tofacitinib - Lin Q; Zhu J; Gao X (Dove Medical Press, 2024)
Qingxia Lin,1 Jinrong Zhu,2 Xuelei Gao3 1Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of China; 2Department of Central Pharmacy, Zhucheng People's Hospital, Weifang, Shandong, People's Republic of China; 3Department of Hepatopancreatobiliary Surgery, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of ChinaCorrespondence: Xuelei Gao, Department of Hepatopancreatobiliary Surgery, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of China, Email gaoxuelei17@163.comAbstract: Vitiligo is a skin depigmentation disease resulting from melanocyte destruction and often co-occurring with autoimmune disorders like hyperthyroidism, alopecia areata, pernicious anemia, and systemic lupus erythematosus (SLE). Although various traditional treatments exist for vitiligo, their effectiveness varies considerably. This report presents a unique case of a vitiligo patient with concomitant systemic lupus erythematosus. Remarkably, after a 30-day course of treatment with tofacitinib, complete repigmentation of the white macular rash was achieved, and there were no adverse drug reactions. These findings provide compelling evidence for the efficacy and safety of oral JAK inhibitors, such as tofacitinib, in vitiligo treatment. Additionally, JAK inhibitors can yet be regarded as a promising new treatment option for vitiligo patients with concurrent autoimmune diseases.Keywords: vitiligo, systemic lupus erythematosus, tofacitinib, JAK inhibitors